Profound asphyxia in the premature infant: imaging findings. - Barkovich, A J; Sargent, S K (American Journal of Neuroradiology, 1995)
PURPOSE To investigate imaging findings in premature infants who had profound asphyxia. METHODS CT (three patients), MR (three patients), and ultrasonography (four patients) studies of five patients who had profound asphyxia before the postconceptional age of 32 weeks were retrospectively reviewed. The patients ranged from 1 day to 4 months old at the time of the imaging studies. An autopsy report was available in one patient. The results were compared with reports in the literature of patients with similar injuries at similar ages. RESULTS Abnormalities of the thalami and basal ganglia were present in all infants examined with CT or MR. CT showed low attenuation in the basal ganglia and high attenuation (blood or calcium) in the thalami; thalamic cavitation and low attenuation of the upper brain stem were present in one infant. MR showed T1 and T2 shortening in the thalami in all patients. Variable MR changes were noted in the basal ganglia, ranging from diminished size with normal signal intensity to T1 and T2 shortening with normal size and complete cavitation. T1 and T2 shortening were seen in the dorsal brain stem in one patient. Sonography showed transient or persistent hyperechogenicity in the thalami in three patients and cavitation of the thalami in one patient. Damage to the perirolandic cortex was not present in any patient. CONCLUSION Profound asphyxia before 32 weeks gestational age shows consistent injury to the thalami, basal ganglia, and brain stem that can be detected by all three imaging modalities. The pattern of injury seems to differ from that of partial asphyxia in premature infants and of profound asphyxia in term infants.